Demonstrating complexity with a roleplaying simulation: investing in water in the Indrawati Subbasin, Nepal - Janmaat, J.; Lapp, S.; Wannop, T.; Bharati, Luna; Sugden, Fraser (International Water Management Institute, 2015)
Rural people in Nepal and other developing nations are part of complex, social-ecological systems. Efforts to provide assistance to these people must integrate knowledge from a variety of perspectives. This report documents the use of a role-playing game, supported by an agent-based model, to demonstrate the interaction between migration, social capital and the effectiveness of water storage. The importance of these interactions was highlighted by fieldwork conducted at several sites in the Koshi River Basin. The model underlying the game was a stylized representation based on the Indrawati Subbasin northeast of Kathmandu, Nepal. The report highlights that (a) role-playing tournaments can be an effective way to engage technical and policy experts with the complex interactions between the social and physical dimensions of watershed management; and (b) migration and the economic changes which drive these interactions are forces that need to be accepted, and investments in water storage need to be selected depending on how they fit into these trends.